Optimization of tempering temperature and soaking time of SCM440 steel horn in ultrasonic-assisted metal inert gas welding - Tran-The Chung, Vinh; Thi-Minh Tran, Quynh; Nguyen, Ngoc-Ha; Ha-Quang Ngo, Thinh; Le, Trung-Kien; Nguyen, Thanh-Hai (Frontiers in Mechanical Engineering, 2024)
This study explores the optimization of ultrasonic horn heat treatment conditions for enhanced mechanical quality (Qm). 14The optimal parameters identified are a tempering temperature of 529°C and a 240-minute soaking time, yielding a 1.3% 15 experimental error. Frequency stability during welding is significantly improved, with the optimal horn exhibiting a 16 minimal frequency variation of 64 Hz compared to 90 Hz and 82 Hz for other samples. Hardness varies with tempering 17 temperature, reaching a peak of over 39.3 HRC at 450°C and dropping to 23.8 HRC at 650°C. Microstructural analysis 18 reveals transformations in pearlite, spheroidization, and increased grain sizes in the optimal sample. Carbide precipitation 19 is more pronounced in longitudinal sections and increases with higher tempering temperatures and soaking times. The 20 presence of chromium alloying elements in SCM440 steel contributes to carbide formation. These findings underscore the 21 critical role of heat treatment conditions in optimizing the performance of ultrasonic horns. 22